Arthroscopic Measurements Predict Knee Chondral Lesion Size More Accurately Than Magnetic Resonance Imaging, and Mechanism of Injury Influences Ability of Either Technique to Predict Graft Size - Adeeb Jacob Hanna, B.S; Andres R. Perez, B.A; Henson Destine, B.S; Michael P. Campbell, M.D; Austin Looney, M.D; Dominic Farronato, M.D; Joshua Pezzulo, M.D; Bradford S. Tucker, M.D; Kevin B. Freedman, M.D (Elsevier, 2024)
Purpose: To compare osteochondral defect size measurements and characteristics across magnetic resonance imaging (MRI) and arthroscopy and at the time of osteochondral allograft (OCA) transplantation or autologous chondrocyte implantation (ACI). Methods: Patients who underwent ACI and OCA transplantation at a single institution between 2015 and 2019 were retrospectively identified. Patients were excluded if they had severe osteoarthritis, MRI scans were not available for review, surgical records did not include defect sizing necessary for analysis, or operative reports were not available. Osteochondral lesion characteristics including size were collected preoperatively by MRI and arthroscopy and at the time of definitive open surgical intervention. Subgroup analysis was performed comparing measurement techniques depending on the corrective surgical approach used, as well as depending on the mechanism of chondral injury, to determine whether these factors had any effect on the ability of arthroscopy or MRI to predict graft size. Results: Overall, 136 chondral lesions were addressed, with restoration procedures in 117 patients (mean age, 32.5 years). The average difference between the final graft size and the lesion area measured with index arthroscopy was 116 mm2, whereas the average difference between the final graft size and the lesion size measured with preoperative MRI was 182 mm2 (P < .001). Depending on surgical technique, measurements with MRI were more similar to the final graft size when a patient underwent OCA transplantation versus ACI (P = .007). Depending on the mechanism of injury, MRI measurements of lesions were closer to the graft area when lesions resulted from trauma (P = .047). Conclusions: Chondral lesion size as determined by preoperative MRI is less accurate than arthroscopic measurement. The mechanism of injury leading to chondral damage and degree of damage may influence the ability of MRI and arthroscopy to accurately measure chondral lesions and predict the final graft size used in surgical correction. Level of Evidence: Level III, retrospective cohort study.